Analyzing Factors Influencing Investment Intention in Digital Startup: Investor’s Perspective - hamdani, moh; Fardiana, Nana; Gandara, Eka; Maso, Rizq (Fakultas Ilmu Administrasi Universitas Dr. Soetomo, 2025)
The digital explosion over the past decade has made creating startups easier, yet investors need to be cautious when putting their money on a venture. Despite enthusiasm pouring into startup investments, investors only inject their fund into select startups. Thus, this research focuses on understanding the rationality behind funding digital startup in Indonesia by examining the driving elements impacting their intention. Survey was done to 20 respondents online, then Multiple Linear Regression analysis tested the independent variables; perception of risk, expected return, platform transparency, policy support, and trust along with evaluated business model and industry potential to determine investment intention of the investors. The research finding shows strong founders improves the perception of trust while growing economic sectors and reliable information among investors boost funding intentions. On the other hand, risk perception prevents the investment propensity. However, Some external factors such as policy direction and public perception, influence insignificantly. These findings are consistent with the Theory of Planned Behavior (TPB), that attitude, subjective norms, and perceived behavioral control are factors that determine investment intention. This study contributes theoretically to the investment behavior literature and gives strategic implications to startups, investors, and policymakers in fostering the Indonesian digital startup ecosystem.